LIFESTYLE IN KUTUH VILLAGE, SOUTH KUTA, BADUNG, BALI AS IMPLICATION OF LAND SALE - Farhaeni, Mutria; Suarka, I Nyoman; Dhana, I Nyoman; Ardjani, Ni Luh (E-Journal of Cultural Studies; Volume 10, Number 4, November 2017DO - 10.24843/cs.2017.v10.i04.p02, 2017)
The purpose of this research is to find out the life style in the post-land sale in Kutuh Village, South Kuta District, Badung Regency, Bali. This research begins with an inventory of the people who sell the land and then classified into several lifestyles. The data and information reviewed the lifestyle implications of post-land sales people. This research was conducted by survey and observation method toward the lifestyle of the community after the land sale. Data collection techniques used are in the form of interviews. From the results of the study, it can be concluded that the lifestyle implications of society have been found to describe the existence of lifestyle changes: consumptive society, creative economy society, gender equality in the distribution of land sales and modern household pretext, in addition the people are unable to maintain their ancestral heritage.